SOEP as a Source for Research on Ageing: Issues, Measures and Possibilities for Improvement - Laura Romeu Gordo; Andreas Motel-Klingebiel; Susanne Wurm (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Demographic change is a key consequence of the development of modern societies. The prolongation of life expectancy, shifts of mortality into later life and long-term low fertility rates cause essential changes in population structures - with an increase in the number and proportion of older people as a key feature. The changes in mortality patterns can be seen as a success of modern society. But demographic shifts imply new risks and challenges as well as opportunities for modern societies, as they affect individual life courses as well as societies as a whole. The present low birth rates also predict low birth numbers in the future, since the number of potential mothers decreases. At the same time, life expectancies are not expected to decrease. As a consequence, the relation between old and young people will change in Germany in the next decades. In 2050, just about half of the population will be of working age and more than 30 percent will be 65 years old or older. The number of the 20 to under 65-years-olds will decrease from 50 million to a figure between 35 and 39 million in the next 40 years (Federal Statistical Office, 2006). Furthermore, the working age population will undergo an ageing process, implying that in 2050, nearly 40 percent of the working-age population will be between 50 and 64 years old (Federal Statistical Office, 2006). In order to understand the labour market and the fiscal implications of these population trends, it is very illustrative to analyse the proportion of older individuals in relation to the working population, the so-called old-age dependency ratio. According to the Federal Statistical Office (2006) the old-age dependency ratio will grow from 32 percent in 2005 to 60 or 64 percent by 2050. This projection indicates that in 40 years, for every three persons of working-age in Germany there will be two persons receiving a pension. If we consider the age cut at 67, the results are not much more optimistic, indicating that increasing the legal retirement age alone is not a solution for the sustainability of the public pension systems and for the decrease in the labour force. The proportion of people of very old age is also growing. While the 80+ population was nearly 4 million in 2005, it will grow to 10 million by 2050 (Federal Statistical Office, 2006). This trend has inter alia, important consequences for health care provision. In this demographic context, interdisciplinary research of ageing and later life gains in relevance. Thus, research on ageing becomes an increasingly crucial task for major surveys like the German Socio-Economic Panel (SOEP). As part of the "research infrastructure" they are called upon to invest in its potentials and attractiveness for research on ageing and later life.
Keywords: J14; 330